2014
DOI: 10.1371/journal.pone.0088480
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value of Stem Cell Quantification in Stage II Colon Cancer

Abstract: BackgroundCancer stem cells (CSCs) are a subset of tumor cells with capacity to self-renew and generate the diverse cells that make up the tumor. The aim of this study is to evaluate the prognostic value of CSCs in a highly homogeneous population of stage II colon cancer.MethodsOne hundred stage II colon cancer patients treated by the same surgical team between 1977 and 2005 were retrospectively analyzed. None of the patients received adjuvant chemotherapy. Inmunohistochemistry expression of CD133, NANOG and C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 16 publications
1
12
0
Order By: Relevance
“…The study selection process is described in Figure 1 . A total of 33 studies 5 16 , 19 – 39 published from 2008–2018 and including 35 data sets with 3,959 patients were selected to evaluate the relationship of NANOG expression and tumor prognosis. The average study population size was 113, ranging from 42 to 312 patients.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The study selection process is described in Figure 1 . A total of 33 studies 5 16 , 19 – 39 published from 2008–2018 and including 35 data sets with 3,959 patients were selected to evaluate the relationship of NANOG expression and tumor prognosis. The average study population size was 113, ranging from 42 to 312 patients.…”
Section: Resultsmentioning
confidence: 99%
“…Four studies evaluated non-small cell lung cancer (NSCLC), 5 , 32 34 four evaluated gastric cancer (GC), 9 , 26 , 27 , 38 and five evaluated OSCC; 8 , 15 , 28 , 29 , 36 breast cancer, 6 , 30 , 31 hepatocellular carcinoma (HCC), 7 , 25 , 39 and ovarian cancer (OC) 13 , 21 , 22 were each evaluated in three studies. Esophageal squamous cell carcinoma (ESCC), 10 , 23 colorectal cancer (CRC), 11 , 16 and pancreatic cancer (PC) 12 , 24 were each evaluated in two studies. Nasopharyngeal carcinoma (NPC), 14 astrocytoma, 20 cervical cancer (CC), 37 tongue squamous cell carcinoma (TSCC), 35 and mucoepidermoid carcinoma (MEC) 19 were each evaluated in one study.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on a systematic review of previous work, we found that CD133 expression was highly correlated with poor OS and DFS, indicating that CD133 + CSCs likely have a close relationship with patient survival and tumor relapse. Among the included studies, six selected patients who received curative surgery rather than postoperative therapy (non-AT subgroup) [ 53 , 55 , 58 , 63 , 72 , 73 ]. Eleven evaluated cancer survival and recurrence among patients, all or most of whom underwent both surgical and adjuvant therapy (AT subgroup) [ 50 , 51 , 55 , 58 , 59 , 67 72 ].…”
Section: Discussionmentioning
confidence: 99%